2008
DOI: 10.1007/s10533-008-9245-0
|View full text |Cite
|
Sign up to set email alerts
|

The reserve of weatherable primary silicates impacts the accumulation of biogenic silicon in volcanic ash soils

Abstract: Banana plantlets (Musa acuminata cv Grande Naine) cultivated in hydroponics take up silicon proportionally to the concentration of Si in the nutrient solution (0-1.66 mM Si). Here we study the Si status of banana plantlets grown under controlled greenhouse conditions on five soils developed from andesitic volcanic ash, but differing in weathering stage. The mineralogical composition of soils was inferred from X-ray diffraction, elemental analysis and selective chemical/mineralogical extractions. With increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…Compared to the other land-cover classes, highest ASi concentrations are found in bog peatlands ( Table 1). The range of ASi concentrations found in bog peatlands is consistent with previous observations of very high ASi concentrations in a subarctic wetland of northern Sweden, where concentrations ranged between 10 and 110 g SiO 2 kg -1 , and are of a similar magnitude to those observed in tropical soils underlying a high Si-accumulating plant system (8-58 g SiO 2 kg -1 ) (Henriet et al 2008). This further corroborates the preservation potential of ASi in bog peatlands.…”
Section: Soc and Asi Distribution In Soilsupporting
confidence: 90%
“…Compared to the other land-cover classes, highest ASi concentrations are found in bog peatlands ( Table 1). The range of ASi concentrations found in bog peatlands is consistent with previous observations of very high ASi concentrations in a subarctic wetland of northern Sweden, where concentrations ranged between 10 and 110 g SiO 2 kg -1 , and are of a similar magnitude to those observed in tropical soils underlying a high Si-accumulating plant system (8-58 g SiO 2 kg -1 ) (Henriet et al 2008). This further corroborates the preservation potential of ASi in bog peatlands.…”
Section: Soc and Asi Distribution In Soilsupporting
confidence: 90%
“…Indeed, the BSi accumulation in the soil-plant system is directly governed by the soil weatherable mineral reserves (Henriet et al, 2008a, b). Depending on the type of soil solution (organic layer leachates or mineral soil solutions), the DSi exported from the soil-plant systems could have a biogenic signature in organic soil surface or pedo/lithogenic signature in organomineral and mineral soil (Fig.…”
Section: Scenario 1: Weathering-unlimitedmentioning
confidence: 99%
“…The global Si cycle is influenced by the type of vegetation (Bartoli, 1983;Alexandre et al, 1997;Blecker et al, 2006;Cornelis et al, 2010c), the stage of soil development (Henriet et al, 2008a, b), the climate characterized by specific moisture and temperature (Raven, 1983;White and Blum, 1995), anthropogenic actions (Conley et al, 1993(Conley et al, , 2002, and orogenesis at the geological timescale (Raymo et al, 1988;Exley, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that tropical vegetation can differ in isotopic Si content, depending on the weathering stage of the parent material, indicating a direct link between vegetation Si and weathered Si Henriet et al 2008). Impacts of morphoclimate zonation on the size of the ecosystem BSi reservoir is expected with weathering rates and weathering stage differing between tropical and temperate regions.…”
Section: Hydrologymentioning
confidence: 99%